Typhoid Fever - Mahmud, AK; Chowdhury, AJ; Sarker, ZM; Miah, RA; Saleh, AA; Mandal, RM; Dhakal, GP (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):236-44. The abstract of this article is available on the PubMed website